Pengaruh Penambahan Inhibitor Ekstrak Kulit Kakao (Theobroma cacao) terhadap Laju Korosi Baja Api 5 L pada Medium NaCl 3% dan HCl 3% - Liyana Mardova; Ediman Ginting Suka; Simon Sembiring (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
Corrosion inhibition of low carbon API 5L by cocoa peel extract (Theobroma cacao) in corrosive medium of natrium chloride and hydrochloride acid of 3% has been investigated. The test was carried out by weight loss method. Corrosion rate was tested on low carbon steel with and without the tea leaves extract for 4 days with concentration of 0, 500, 1000, and 1500 ppm. The research result show that the more percentage of cocoa peels inhibitor extract, the lower corrosion rate so that capability of inhibition will increase. The biggest inhibition efficiency corrosion occurred at concentrations of 1500 ppm in NaCl and HCl with efficiency of 93,39% and 73,6% respectively. The X-Ray Diffraction (XRD) result shows that the phase was Fe. Scanning Electron Microscopy (SEM) shows that the grain size and cluster is bigger, hole and crack also shows is lower of with inhibitor than without inhibitor. Energy Dispersive Spectroscopy (EDS) shows that there is Cl element on sample without inhibitor.